BURSA EFEK GLOBAL DAN PENGARUHNYA TERHADAP BURSA EFEK INDNESIA PASCA KRISIS KEUANGAN 2008 - Ibnu Khajar (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
The global financial crisis has negatip effect on global capital markets include Indonesian Capital market (IDX). This aims of this research are, first, to, to knowing effect of global stock market to Indonesian Capital Maket. Second, to analyze how performance of each Global Capital Marketcompare with each others, than analyze wich are the best and worst market. The types of this research were descriptive and explanatory research and the research method with used seconder data and purposive sampling technique. The samples in this research are indexes of global capital markets, like as: DJI, NIKKEI, KOSPI, HSI, FTSE, ASX and JKSE (IHSG). Thedata collection technique is the literature study and documentation, while the data analysis technique is with Eviews. The results of this research indicated that (1) There are significantly simultan relationship between global capital markets (DJI, NIKKEI, KOSPI, HSI, FTSE and ASX) to Indonesian capital market (IHSG), and three global capital markets (DJI, FTSE and HSSI)has significant partial impact to IHSG. (2) There isn’t defference significance performance between each capital market in the global capital market. And (3) Indonesian capital market has highest average market return.Keywords: Global financial crisis, indexes of global capital, market return